Comparison Of The Incarnation Of God From The Christian Perspective (The Word) With The Incarnation From The Hindu Perspective (Avatar) - Jimmy Marshal Tambunan; Ryan S. G. Sinaga; Maruhum Simangunsong; Halomoan Marpaung (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the concept of Jesus as the Word who became flesh in the Christian tradition and compares it with the concept of divine manifestation (avatar) in Hinduism. The background of this research is based on the importance of a deeper understanding of the core doctrines of Christianity, particularly regarding the incarnation of Jesus Christ, in the context of a pluralistic society with diverse religious beliefs. This comparative study also aims to examine the similarities and differences in understandings of God's presence in human life based on the theological perspectives of each religious tradition. The results of the study indicate that, from a Christian theological perspective, Jesus Christ is understood as the Word of God who became flesh through the event of incarnation. This incarnation is believed to have occurred once and for all as a manifestation of God's love for humanity and is the primary basis for human salvation from sin. The presence of Jesus in history is understood not merely as a temporary appearance or manifestation, but as the presence of God in the person of Jesus Christ, who has both divine and human dimensions. Thus, the incarnation holds a very important position in the Christian teaching of salvation. On the other hand, in Hindu belief, the concept of avatar refers to the manifestation or incarnation of God, especially Vishnu, in various forms and shapes to restore cosmic balance, uphold dharma, and overcome adharma. These divine manifestations can occur repeatedly according to the needs and conditions of the world. Although there are fundamental differences in the number, form, nature, and purpose of divine incarnations, both concepts share a common understanding that God is not seen as entirely passive towards human life. Both depict the active involvement of the divine in history and human life with the aim of bringing salvation, order, moral restoration, and goodness. However, these similarities do not eliminate fundamental theological differences, particularly regarding the uniqueness of the incarnation of Jesus in Christianity and the recurring nature of the avatar concept in the Hindu tradition.